(untitled) (Proceedings of The International Conference on Economics and Development, 2019)
Merging two distinct disciplines, the term Entrepreneurial Marketing (EM) is used to describe the marketing process of small firms pursuing opportunities under limited resource conditions and uncertain market circumstances. The aim of this study was to explore the Entrepreneurial Marketing approach adopted by Small and Medium Scale Enterprises (SMEs) in a selected divisional secretariat division of Sri Lanka. A sample of 90 SMEs were selected using disproportionate stratified random sampling and data were collected using a structured questionnaire. Results revealed that the majority of the SMEs exhibit a moderate level of adoption of EM, while showing the highest and lowest level of adoption towards value creation and innovativeness respectively. Results also revealed that there is a significant relationship between business size, business age and education level of the business operator and the level of adoption of EM. Further, as per the findings, the overall EM and three EM dimensions (value creation, proactiveness and innovativeness) has a positive correlation with the sales growth of the business.